2009
DOI: 10.1152/ajprenal.90518.2008
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced contraction is attenuated by nitric oxide in afferent arterioles from the nonclipped kidney in 2K1C

Abstract: , one-clip (2K1C) is a model of renovascular hypertension where we previously found an exaggerated intracellular calcium (Ca i 2ϩ ) response to ANG II in isolated afferent arterioles (AAs) from the clipped kidney (Helle F, Vagnes OB, Iversen BM. Am J Physiol Renal Physiol 291: F140 -F147, 2006). To test whether nitric oxide (NO) ameliorates the exaggerated ANG II response in 2K1C, we studied ANG II (10 Ϫ7 mol/l)-induced calcium signaling and contractility with or without the NO synthase (NOS) inhibitor N G -ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
27
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 31 publications
11
27
1
Order By: Relevance
“…We concluded that Ang II activates PI3K/ Akt1 via the AT 2 receptors, inducing phosphorylation of NOS3 at serines 1177 and 633, resulting in increased production of NO by the TAL. NO has been shown to buffer the actions of Ang II within the renal medulla (5,(45)(46)(47)(48)(49). In the TAL, NO inhibits (15,50), reabsorption whereas O 2 Ϫ stimulates Na ϩ reabsorption (51).…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that Ang II activates PI3K/ Akt1 via the AT 2 receptors, inducing phosphorylation of NOS3 at serines 1177 and 633, resulting in increased production of NO by the TAL. NO has been shown to buffer the actions of Ang II within the renal medulla (5,(45)(46)(47)(48)(49). In the TAL, NO inhibits (15,50), reabsorption whereas O 2 Ϫ stimulates Na ϩ reabsorption (51).…”
Section: Discussionmentioning
confidence: 99%
“…Combined inhibition of nitric oxide synthesis and ANG II stimulation uncovers a decreased contractility and almost no nitric oxide production in vessel preparations from animals with heart failure (26). This shows a marked difference from the effect of ANG II on afferent arterioles in high renin hypertension models (22,24) and during ANG II blockade in vivo (61). ANG II increases tubular sodium reabsorption (47), although reabsorption may be decreased by ANG II in the proximal nephron (37,64).…”
Section: Renin-angiotensinmentioning
confidence: 96%
“…ANG II is a key hormone in the regulation of RBF and GFR. However, its effect is in many situations balanced by vasodilators such as vasodilatory prostanoids and nitric oxide (NO) (6). Together these signaling substances are of major importance in the regulation of RBF in the normal kidney and probably more so in hypertensive models where the components of the reninangiotensin system are activated or increased.…”
mentioning
confidence: 99%
“…We have recently shown that ANG II-induced NO release controls renal vascular resistance by its ability to adjust the diameter of preglomerular vessels in the nonclipped kidney of two-kidney, one-clip hypertensive (2K1C) animals (6). The nonclipped kidney is subjected to high perfusion pressure and high vascular NO release, while vascular NO production is low in the clipped kidney.…”
mentioning
confidence: 99%